2020
DOI: 10.17478/jegys.669034
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Aspiration and Interest towards STEM and TVET Careers among Lower Secondary Students: A Malaysian Case Study

Abstract: Education system in Malaysia continues to develop and expands to meet the demands of 21 st century that strongly advocates the use of technology in teaching and learning. As such, basic education gives greater emphasis on two fields; STEM (Science, Technology, Engineering & Mathematics) and TVET (Technology & Vocational Education Training) in order to encourage school students to pursue higher education in STEM and TVET fields; however, the aspiration and interest to pursuit higher education in both fields are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
1
8
0
2
Order By: Relevance
“…Based on the research results by Morrison ( 2006 ) in the United States, STEM was found to enhance student creativity, their ability at creative design, and the production of solutions based on current needs. This is consistent with Bakar and Mahmud ( 2020 ), who detailed the national government's stated importance of STEM and TVET education in Malaysia.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the research results by Morrison ( 2006 ) in the United States, STEM was found to enhance student creativity, their ability at creative design, and the production of solutions based on current needs. This is consistent with Bakar and Mahmud ( 2020 ), who detailed the national government's stated importance of STEM and TVET education in Malaysia.…”
Section: Discussionsupporting
confidence: 89%
“…This is a strong reason that the teacher is declared as a professional in the process of pouring the concept of knowledge. Through a clear concept, the aim of vocational education cannot be separated from its trajectory, namely as a solution in reducing unemployment [21,22], thus giving birth to a new economy [23,24]. All study discussions in the scope of technology including the TPACK concept were packaged by Mishara & Koehler [12].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the findings in this study that students from those streams have a favourable impression of TVET can be supported. Bakar and Mahmud (2020) also mentioned that 12% of Science stream students pursue vocational education for their tertiary education.…”
Section: Figure 2 Proportion Of Gendermentioning
confidence: 99%